2014
DOI: 10.1007/s40496-014-0038-3
|View full text |Cite
|
Sign up to set email alerts
|

Rheumatoid Arthritis and Periodontal Disease: A Rheumatologist's Perspective

Abstract: Despite advances in our understanding of the inflammatory events that underlie rheumatoid arthritis (RA), which have led to targeted therapies that more effectively control the condition, the etiology of RA is not fully understood. With the discovery that serum antibodies to citrullinated peptides (ACPA) are highly specific for RA and that Porphyromonas gingivalis, the major pathogen responsible for periodontitis (PD), contains the enzyme responsible for the citrullination of peptides, a plausible explanation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 116 publications
(107 reference statements)
0
3
0
Order By: Relevance
“…They function as immune regulatory cells in the circulation and differentiate into osteoclasts at the local pro‐osteoclastogenic environment. However, given the increasing evidence suggesting systemic inflammatory bone loss diseases, such as rheumatoid arthritis, as a risk factor for chronic periodontitis and vice versa, it is not unreasonable to hypothesize that increased osteoclast precursors are involved in the association of chronic periodontitis and various inflammatory bone loss diseases . Indeed, patients with active erosive arthritis have a marked increase in the frequency of peripheral blood CD11b + osteoclast precursors .…”
Section: Discussionmentioning
confidence: 99%
“…They function as immune regulatory cells in the circulation and differentiate into osteoclasts at the local pro‐osteoclastogenic environment. However, given the increasing evidence suggesting systemic inflammatory bone loss diseases, such as rheumatoid arthritis, as a risk factor for chronic periodontitis and vice versa, it is not unreasonable to hypothesize that increased osteoclast precursors are involved in the association of chronic periodontitis and various inflammatory bone loss diseases . Indeed, patients with active erosive arthritis have a marked increase in the frequency of peripheral blood CD11b + osteoclast precursors .…”
Section: Discussionmentioning
confidence: 99%
“…Specifically examining RA, Scher et al 1 noted that >75% of patients with RA have moderate‐to‐severe periodontal disease. Many studies have suggested an association between periodontal disease and RA, 1–10 whereas others have disagreed 11–14 . Similarly, association of periodontal disease with ankylosing spondylitis (AS) has been suggested 15–17 …”
mentioning
confidence: 99%
“…All previous studies 1–18 represent evaluation of patients in the second half and typically in the last quarter of the twentieth century. Non‐steroidal anti‐inflammatory drugs (NSAIDs), corticosteroids, immunomodulatory drugs, and, of course, biologics were not available in the first half of the twentieth century 26 .…”
mentioning
confidence: 99%